Autoconceito, bullying e preconceito: uma análise a partir de estudantes de escolas públicas - Céos, Cysney Pétala (2020)
This dissertation sought to analyze relationships between Self-Concept, Bullying and Prejudice among students from public schools. To achieve this goal, three chapters were developed in the form of articles. Chapter 1, a theoretical article, conceptualized the variables Self-concept, Bullying and Prejudice, understanding the points of interaction existing between phenomena. In this chapter it was possible to observe that prejudice and bullying, although imbued with similar aspects, are different constructs and, therefore, lack different interventions. Moreover, the text explained that immersion in bullying situations produces and receives influence from the dimensions of self-concept, and this interference is distinct to depend on the role occupied by the student in this type of school violence. While the authors of bullying have high social and physical self-concept, targets tend to have positive prominence in the family and academic dimensions of self-concept. Chapter 2, an integrative review of empirical articles between 2008 and 2018, described the méthodologique profile and the main results of publications involving self-concept and bullying among students. The results obtained in this chapter indicated a relationship between self-concept and bullying, evidencing that the various aspects/dimensions of self-concept interact with such a form of violence and the roles that occur thereof. It was evidenced that the female public has a low level of self-concept in most of its dimensions, suffering more from the consequences of bullying both in the target role and in the role of author, when compared to the male audience. Chapter 3, an empirical study, investigated the relationship between the dimensions/factors familiar, academic, social and physical of selfconcept with bullying and prejudice in a sample of 284 adolescent students from the ninth year of elementary school from eight Sergipe public schools. The results obtained in this study indicated that the male public stands out positively when analyzing the physical, social and family dimensions of the self-concept. Moreover, it was evidenced that, in situations of bullying, the physical dimension is related to the authors of aggressions, while the academic dimension is related to the targets. Despite the interaction between self-concept and manifestation of prejudice, the results showed no influence between them.